Sequencing and Functional Annotation of mRNAs and lncRNAs from Tea (Camellia sinensis) Leaves During Infection by the Fungal Pathogen Lasiodiplodia theobromae - Dongxue Li; Silong Jiang; Xiaodong Wen; Xingchen Song; Yuanyou Yang; Yu Wang; Honglin Huang; Delu Wang; Zhuo Chen (PhytoFrontiers, 2021)
Due to the absence of effective control measures, tea leaf spot, caused by Lasiodiplodia theobromae, can seriously reduce the production and quality of tea leaves. Analysis of the relationship between messenger RNAs (mRNAs) and long noncoding RNAs (lncRNAs) of tea could help to prevent and control the disease. In this current study, high-performance sequencing of mRNA and lncRNA from tea leaves during infection by L. theobromae was conducted using the Illumina HiSeq 4000 platform. Of the differentially expressed mRNAs, 2,503 or 5,278 were significantly up- or down regulated, respectively, in challenged leaves relative to unchallenged leaves. Differentially expressed lncRNAs were also analyzed at the level of genes for the above two treatments. The numbers of significantly up- or downregulated lncRNAs were 3,403 or 1,477, respectively. Functional analysis of mRNA revealed that L. theobromae challenge can induce the upregulation of the genes of seven transmembrane MLO family protein -3, -6, -11, major allergen Pru ar 1, and so on. In total, 176 differentially expressed lncRNAs occurred in response to L. theobromae challenge as a result of cis regulation, with 146 differentially expressed mRNAs. At the biological process of defense response, the glycosyl hydrolase 9A1 gene was cis regulated by the differentially expressed lncRNA. The expression profiling and association studies of the tea host infected by L. theobromae will provide a resource for future research into host–pathogen interactions and disease resistance.[Figure: see text] Copyright © 2021 The Author(s). This is an open access article distributed under the CC BY-NC-ND 4.0 International license.